Design of a Boolean Information Retrieval Model in an Android-Based Qur’an Interpretation Application - Ahmad Yani (Institute of Information Technology and Social Science (IITSS), 2025)
Technological developments have had a significant impact on human life, including the learning process. The modern digital era has produced a wide range of devices that have indirectly reduced public interest in reading, including reading the Holy Qur’an. The COVID-19 pandemic further exacerbated this condition because religious learning activities that were previously conducted in places of worship were forced to shift to online learning. The Ministry of Religious Affairs of the Republic of Indonesia (Kementerian Agama Republik Indonesia) has provided a digital Qur’an application; however, it does not yet include a fast and accurate interpretation search feature. This study aimed to develop an Android-based Qur’an interpretation application by implementing a Boolean Information Retrieval (IR) model as the method for searching the interpretation index. The application was developed using the Dart programming language and the Flutter framework, with reference to Tafsir Ibn Kathir. The results indicate that the implementation of the Boolean IR model improved the effectiveness of interpretation searches and generated relevant results in accordance with user needs.